2002
DOI: 10.1002/cne.10223
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐induced dendritic spine elimination on female rat ventromedial hypothalamic neurons that project to the periaqueductal gray

Abstract: Neurons of the ventromedial hypothalamic nucleus (VMH) that project to the periaqueductal gray (PAG) form a crucial segment of the motor pathway that produces the lordosis posture, the hallmark of female rat sexual behavior. One suggested mechanism through which estrogen facilitates lordosis is by remodeling synaptic connectivity within the VMH. For instance, estrogen alters VMH dendritic spine density. Little is known, however, about the local VMH microcircuitry governing lordosis nor how estrogen alters syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 92 publications
3
58
0
Order By: Relevance
“…There is evidence for gonadal hormone stimulation of neurogenesis (Breedlove et al, 1983;Nordeen et al, 1985) and apoptosis (Nilsen et al, 2000), synapse formation (McEwen et al, 2001) and synapse elimination (Calizo and Flanagan-Cato, 2002), neuropeptide expression (De Vries, 1990), and glial modulation (Drew and Chavis, 2000;McCarthy et al,2002). The seemingly ubiquitous and contradictory nature of all of these actions has confounded the development of a singular mechanistic hypothesis that accounts for the effects of gonadal hormones in the modulation of nociceptive sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for gonadal hormone stimulation of neurogenesis (Breedlove et al, 1983;Nordeen et al, 1985) and apoptosis (Nilsen et al, 2000), synapse formation (McEwen et al, 2001) and synapse elimination (Calizo and Flanagan-Cato, 2002), neuropeptide expression (De Vries, 1990), and glial modulation (Drew and Chavis, 2000;McCarthy et al,2002). The seemingly ubiquitous and contradictory nature of all of these actions has confounded the development of a singular mechanistic hypothesis that accounts for the effects of gonadal hormones in the modulation of nociceptive sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is possible that by differentially increasing or decreasing spine density on different portions of the dendritic tree, estrogen may finetune synaptic inputs to VNMvl neurons in a way that facilitates lordosis or other female sexual behaviors. In support of this suggestion, subsequent research has shown that the estrogen-responsive VMNvl neurons with long ventrolateral dendrites are projection neurons that send axons to the midbrain periaquaductal gray (PAG; Calizo and Flanagan-Cato, 2002), a connection essential in mediating the lordosis posture (Sakuma and Pfaff, 1979;Hennessey et al, 1990).…”
Section: The Ventromedial Nucleus Of the Hypothalamusmentioning
confidence: 92%
“…The two studies are even more consistent if you consider the possibility that the cells accumulating [ 3 H] testosterone may be labeling cells expressing estrogen receptors as well as androgen receptors, since testosterone could have easily been aromatized into 17 beta-estradiol before binding to the preoptic cells. Interestingly, in the ventromedial nucleus of female rats, cell types defined based on the expression of estrogen receptor-alpha and a high density of spines have also been found to preferentially project to the PAG and these specific defined projections have been related to the hormonal activation of female-typical sexual behaviors (Calizo and Flanagan-Cato, 2002). However, comparable studies in males were not conducted in this case.…”
Section: Comparison With Other Studies Of Sex Differences In Hodologymentioning
confidence: 95%